Measurement of the muon anti-neutrino charged current double differential cross section with no pions in the final state on water using the pi-zero detector at T2K - Campbell, Thomas, author; Toki, Walter, advisor; Biedron, Sandra, committee member; Buchanan, Norm, committee member; Wilson, Robert J., committee member (Colorado State University. Libraries, 2018)
The T2K (Tokai to Kamioka) experiment is a long baseline neutrino oscillation experiment where a narrow band (by energy) neutrino beam of primarily muon neutrinos or muon anti-neutrinos is produced in Tokai and directed towards Kamioka in Japan. Neutrinos in the beam are first detected at the T2K near detector complex 280 m from the beam source (ND280) and then travel 295 km before being detected again at the Super-Kamiokande (Super-K) water-Cherenkov detector. In addition to measuring the flux of neutrinos in the T2K beamline en route to Super-K, other physics analyses are performed at ND280. This thesis describes one such measurement where the π0-detector (P∅D) and a time projection chamber at ND280 were used to measure the charged-current cross section for muon anti neutrinos with water as the interaction target and no pions in the final state. Such a cross section is a T2K and world first. This cross section was measured differentially by the outgoing lepton true kinematics using a binned likelihood fitting framework recently developed at T2K. The thesis will provide: an introduction to neutrinos in the context of a cross section measurement, a description of the T2K experiment including common software tools used in analysis, a general discussion of concerns in differential cross section measurements, a mathematical formulation of the likelihood fitting procedure, details of the neutrino event selection process, the chosen parameterization and validation of the fit, and finally, the cross section results in data with a discussion of the significance and conclusions of the measurement. The total cross section integrated over all differential bins considered in the analysis is measured to be: σ = (7.844 ± 1.316) × 10−39 cm2/water molecule.